PENGARUH RETURN ON ASSET, CURRENT RATIO, DEBT TO EQUITY RATIO DAN SIZE TERHADAP NILAI PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Miandari, Marsya; Andriyani, M Ima; Noviantoro, Djatmiko (LPPM Universitas Multi Data Palembang, 2025)
Abstract: This research aims to determine and prove the influence of Return On Assets, Current Ratio, Debt To Equity Ratio and Size on the value of banking companies on the Indonesian Stock Exchange for the 2018-2022 period, either partially or simultaneously, the population consists of 46 types of banking companies in Indonesia. registered or gone public on the Indonesia Stock Exchange. The sampling technique in this research is purposive sampling. Purposive sampling refers to a sampling method that is based on special criteria, certain characteristics, or characteristics that are appropriate to the nature of the population, so that the data that meets the sampling characteristics is 11 banking companies. Data analysis used in this research was with the help of Eviews 13 software. The results of this research show that (1) The Return On Asset variable has a positive and significant effect on Company Value, (2) The Current Ratio variable has a positive and significant effect on Company Value, (3) The Debt To Equity Ratio variable does not have a positive and significant effect on Company Value, (4) The Size variable has a positive and significant effect on Company Value, (5) The variables Return On Asset, Current Ratio, Debt To Equity Ratio and Size have a positive and significant effect on Company Value. Keywords: Return On Assets, Current Ratio, Debt To Equity Ratio, Size, Company Value